2011
DOI: 10.1007/s10653-010-9371-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of groundwater quality and its suitability for drinking, domestic, and agricultural uses in the Banana Plain (Mbanga, Njombe, Penja) of the Cameroon Volcanic Line

Abstract: Groundwater quality of the Banana Plain (Mbanga, Njombe, Penja-Cameroon) was assessed for its suitability for drinking, domestic, and agricultural uses. A total of 67 groundwater samples were collected from open wells, springs, and boreholes. Samples were analyzed for physicochemical properties, major ions, and dissolved silica. In 95% of groundwater samples, calcium is the dominant cation, while sodium dominates in 5% of the samples. Eighty percent of the samples have HCO(3) as major anion, and in 20%, NO(3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 27 publications
7
43
0
Order By: Relevance
“…A negative value indicates under saturation with respect to the particular mineral and the mineral cannot precipitate from solution, and should dissolve if present, into solution to reach equilibrium concentration (Deutsch 1997). Also, in the case of groundwater with values of SI less than zero indicates water from formation with insufficient quantity of mineral for solution or short residence time (Ako et al 2011). Values above zero indicate super saturation with respect to the particular mineral phase and incapable of dissolving more of the mineral and water discharging from an aquifer containing sufficient amount of the mineral species with longer residence time to reach equilibrium in the case of groundwater (Ako et al 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A negative value indicates under saturation with respect to the particular mineral and the mineral cannot precipitate from solution, and should dissolve if present, into solution to reach equilibrium concentration (Deutsch 1997). Also, in the case of groundwater with values of SI less than zero indicates water from formation with insufficient quantity of mineral for solution or short residence time (Ako et al 2011). Values above zero indicate super saturation with respect to the particular mineral phase and incapable of dissolving more of the mineral and water discharging from an aquifer containing sufficient amount of the mineral species with longer residence time to reach equilibrium in the case of groundwater (Ako et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Also, in the case of groundwater with values of SI less than zero indicates water from formation with insufficient quantity of mineral for solution or short residence time (Ako et al 2011). Values above zero indicate super saturation with respect to the particular mineral phase and incapable of dissolving more of the mineral and water discharging from an aquifer containing sufficient amount of the mineral species with longer residence time to reach equilibrium in the case of groundwater (Ako et al 2011). Appl Water Sci (2017) 7:961-985 967 Table 1 Ionic composition of sampled surface water in study area (river, pond and stream locations are shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the incongruent dissolution of silicate minerals that react with dissolved CO 2 gas derived directly from the atmosphere, decay of organic matter in the soil or photosynthesis results in the release of major cations, bicarbonate and dissolved silica [36]. Comparable findings have been reported in some natural waters of Cameroon [21,[37][38]27]. These authors attributed the solute composition of natural waters to the hydrolysis of the rock-forming minerals and the incongruent weathering reactions.…”
Section: Regional Spatial Distribution and Sources Of Enriched Geochementioning
confidence: 99%
“…In groundwater hydrology, the bomb produced tritium signal has effectively been used for qualitative dating of young ground waters based on the existence or absence of the bomb anomaly (Fritz and Fontes, 1980;Clark and Fritz, 1997), and by analyzing the decay of natural tritium in the subsurface environment (Kazemi et al, 2006). Ako et al (2011) evaluated groundwater quality in Mbanga, Njombe and Penja (Banana Plain) and its suitability for drinking, domestic and agricultural uses. They established a close relationship between agro-industrial activities in the area and nitrate contamination of the groundwater resources but other hydrogeochemical processes controlling their chemistry, their origin(s) and residence times were not elucidated.…”
Section: Introductionmentioning
confidence: 99%